Analisis Pendapatan Usahatani Sayuran Hidroponik S2r Farming Di Desa Warukapas Kecamatan Tatelu Kabupaten Minahasa Utara - Agnes Monica Siahaan; Melsje Yellie Memah; Audrey Julia Maria Maweikere (Sam Ratulangi University, 2022)
This study aims to determine the profitability and feasibility of S2R Farming hydroponic vegetable farming in Warukapas Village, Tatelu District, North Minahasa Regency. This research was conducted for 2 months, from March to April 2022. The data analysis method used in this study was quantitative analysis. The quantitative analysis used is the analysis of farm profits by calculating the difference between revenue and production costs in one production for 40 days and analyzing the feasibility of the R/C ratio and calculating the Break Event Point (BEP) of S2R Farming. The data used are primary data and secondary data. Primary data were obtained through direct interviews between researchers and business owners, through observation and interviews using direct questionnaires at the S2R Farming research location. Secondary data obtained from books, internet, thesis, journals and other sources. The results showed that the profit of S2R Farming vegetable farming in one production for 40 days was Rp 7,423,427,05, with an R/C value of 2,060. The Break Even Point (BEP) value of S2R Farming vegetable farming is Rp 3,388,769.13. The amount of production that must be obtained by S2R Farming vegetable farming in Warukapas Village in order to break even is 247 packs of pakcoy vegetables and 223 packs of lettuce. So that S2R Farming vegetable farming in Warukapas Village is profitable and feasible to work on.